Identification of deregulation in protein expression level of erlotinib-resistant H1299 cell lines - Mat Daud, Syukriyah (2015)
Erlotinib, a small-molecule epidermal growth factor receptor (EGFR) tyrosine kinase inhibitor, has been shown to be an effective solution in treating non-small cell lung cancer (NSCLC). However, most patients who initially show a good response to erlotinib treatment eventually develop resistant and experience progressive disease. There is no absolute answer on how the cells can develop resistance against the erlotinib. It was suggested that changes in the cell cycle could contribute to the acquired resistance of NSCLC. In this study, untreated H1299 and erlotinib-resistant H1299 (H1299-R) were used to compare proteins expression levels involved in cell cycle. The main cell cycle players that were investigated included Cyclin A and E, Cyclin-dependent kinases (CDK) 2, 4, and 6, p21, NFKB, and ß-actin. A calourimetric method, alkaline phosphatase, was used to detect the amount of proteins present in the sample. Although the concentration of the protein loaded into the gel was increased from 75 μg to 85 μg, the results obtained were similar. Both cell lines possessed ß-actin and Cyclin A proteins only.